The role of saliva in the process of oxidative stress – review of literature - Krysińska, Anna; Wojnar, Małgorzata; Hermanowicz, Adam; Matuszczak, Ewa (Journal of Education, Health and Sport, 2016)
Background: Saliva constitutes a first line of defence against free radical-mediated oxidative stress, since the process of mastication and digestion promotes lipid peroxidation. During gingival inflammation, gingival crevicular fluid flow increases the change of saliva composition with products from the inflammatory response, modulating oxidative damages in the oral cavity. Authors review the current literature concerning the reactive oxygen species, oxidants, pro-oxidants and antioxidants in saliva, and methods for assessing the antioxidant capacity of saliva. Comparison of salivary antioxidant status in male and female subjects reveales a significant gender-related difference in saliva composition. The current data demonstrate a significant enhancement of the salivary antioxidant system in juvenile idiopathic arthritis patients. Also patients with chronic renal failure, diabetes and on hemodialysis show increase oxidative stress burden in both serum and saliva. The finding of reduced oral peroxidase levels in smoking subjects may represent a contributory mechanism for initiation and progression of cigarette smoke-related oral diseases such as oral cancer. The results of recent studies indicate that the total antioxidant capacity of saliva decreased in children with HIV infection. Conclusion: Whole saliva may contain simply measured indicators of oxidative processes. This may provide a tool for the development and monitoring of new treatment strategies. A non-invasive determination of the salivary concentrations of antioxidants such as superoxide dismutase (SOD) and uric acid (UR) allows the evaluation of the defensive capacity of the oral mucosa. Still, there is a need for standardization of methods for saliva sampling and testing protocol.